A Ten-Year Review of Carbapenemase Producing Enterobacterales (CPE) in London, United Kingdom. (October 2020) - Patel, Bharatkumar; Hopkins, Katie; Meunier, Daniele; Staves, Peter; Hopkins, Susan; Woodford, Neil
Abstract : Background: To determine the pattern of CPE observed in a single region in the United Kingdom. Methods: From 2009 to 2018, clinical laboratories in England were requested to send suspected CPE from all sites to the national reference laboratory for confirmation and investigation of carbapenem resistance mechanism(s). Isolates of Enterobacterales from London laboratories and confirmed to have 1 or more carbapenemase genes were included in the analysis. Result: Between 2009 and 2018, 5, 133 isolates were confirmed to produce a carbapenemase; at least 1 CPE was identified in every London Laboratory and hospital. Confirmations increased from 28 isolates in 2009 to 1857 in 2018 and with a sharp rise after the introduction of the 'PHE toolkit' in 2013 (Fig. 1). Most CPE (2655, 51.7%) were from rectal screens (the 3 most frequently identified carbapenemase families were OXA-48–like in 1, 263 isolates, NDM in 971 and IMP in 128), 631 (12.3%) were from urine samples, 180 (3.5%) from blood cultures, 103 (2.0%) from sputum specimens and the remainder (1564, 30.5%) were swabs, fluids and tissues from various body sites. Moreover, 51 CPE (1%) were identified from environmental swabs. Isolates were predominantly Klebsiella spp (2, 525, 49%; 2, 088 were K. pneumoniae ), followed by Escherichia coli (1, 434, 27.9%), Enterobacter spp (746, 14.5%; 605 were E. cloacae complex), and Citrobacter spp (349, 6.8%); 10 other species contributed smaller numbers. Within the carbapenemase families, OXA-48-like enzymes predominated overall (2303, 44.9%), followed by NDM (1822, 35.5%), IMP (313, 6.1%), VIM (207, 4.0%), NDM+OXA-48-like (205, 4.0%), and KPC (196, 3.8%). The first detection of a CPE with 2 distinct enzymes occurred in 2012 (OXA-48-like and NDM) and since then 235 co-detections have been identified; 233 related to OXA-48-like with another gene. Conclusion: The first CPE isolate in London was identified in 2003, a Klebsiella spp with a VIM enzyme. The number of isolates submitted to the national reference laboratory has continued to increase year on year. VIM and NDM carbapenemases predominated in the early years, because of their association with several outbreaks; these have now been overwhelmed by OXA-48-like detections and outbreaks. The increasing numbers of CPE with a combination of a metallo- and a non-metallo carbapenemase increases the therapeutic challenges to treat infected patients. Bacteremia caused by CPE remains rare, suggesting that infection prevention and control efforts are having some impact. However, as colonization prevalence increases, the number of clinical infections will rise in the future unless control measures to limit transmission and spread are improved. Funding: None Disclosures: None